KEPUTUSAN PEMBELIAN BARANG SECARA ONLINE DITINJAU DARI ASPEK PROMOSI DAN KEPERCAYAAN KONSUMEN - Abdul Wakil (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2021)
Abstract The purpose of this research is to analize the impact of promotion and consumer trust on online purchasing decision. The type of this research is a quantitative research using multiple regression analysis. The population in this research are all Tokopedia marketplace consumers. The sampling method used in this research is purposive random sampling as many as 50 people. The results of this research showed that promotion has a positive and significant effect on online purchasing decision, consumer trust has a positive and significant effect on online purchasing decision. Keywords : Promotion ; Consumer Trust ; Online Purchasing Decision